Social sustainability and reading promotion: linkages between public policies and quality education in Brazil - Camillo, Everton da Silva [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2024)
This paper was aimed at knowing to what extent the Brazilian public policies Plano Nacional do Livro e Leitura and Politica Nacional de Leitura e Escrita merge with the United Nations Sustainable Development Goal 4 of quality education, namely Quality Education, from a social sustainability perspective. A mixed-methods approach was required for this purpose due to both quantitative and qualitative approaches to dealing with the data. We chose the Content Analysis research method to analyze them. Specifically, we used the categorical analysis technique and established a coding scheme. The policies Plano Nacional do Livro e Leitura and Politica Nacional de Leitura e Escrita merge with only three out of ten Sustainable Development Goal 4 targets, being: (a) to guarantee meaningful learning processes (4.1 target); (b) to offer scholarships for professional development (4.b target); and (c) to develop teacher training programs (4.c target). However, other linkages not related to the Sustainable Development Goal 4 were observed. They concern the following: (a) copyright and book economy matter; (b) social reading practices; (c) learning environments where to promote reading; (d) research and studies on the book production chain and information consumption market; (e) the use of technology to enhance reading promotion practices; and (f) symbolism during activities of reading promotion. The study concludes that despite the potential of Brazilian public policies for reading promotion to leverage quality education within the realm of social sustainability, the documents analyzed do not exhibit significant correlations with Sustainable Development Goal 4 of the 2030 Agenda. This suggests that the Plano Nacional do Livro e Leitura and Politica Nacional de Leitura e Escrita should incorporate the seven missing requirements of the Quality Education Sustainable Development Goal (4.2, 4.3, 4.4, 4.5, 4.6, 4.7, and 4.a target), demonstrate all the ten targets, and establish a reading policy based on sustainable development until 2030.
Keywords: sustainable development; 2030 Agenda; policymaking; reading policy; policy analysis